Performance evaluation of mdora protocol in vehicular ad-hoc networks - Mohammed, Dania; Ghanim Wadday, Ahmed (International Journal of Engineering & Technology, 2018)
the successful solutions used to manage traffic at intersections is the Vehicular ad hoc Network (VANET). The main problems in VANET are the preparation of the blocked route, repeated topology differences, and continuous vehicle movement. These problems are difficult to route data towards destinations. To work around this problem, use the Position-Based Routing Protocol (MDORA) name. One of the objectives of this protocol is to choose the best way to rely on the jump by the jump and on the footing of the farthest dis-tance of the interface from the source, thus ensuring the full transfer of data. This protocol reduces frequent connections by detecting the following packets and sending packets without first discovering the path. The environment is simulated by the Matlab program to show protocol results. The random distribution of nodes generation in the simulation environment has been changed in order to change con-tract locations compared to the first state of simulation and to show new result in second state of the protocol. as well The time unit value is also changed to reach the ratio of the number of dropped packets.Â Â